Macroscopic Hematuria and a Bladder Mass: Eosinophilic Cystitis in a 7-Year-Old Boy - Stine Bjerrum Runge; Søren Høyer; Louise Winding (Case Reports in Radiology)
We report a case of eosinophilic cystitis in a 7-year-old boy with a history of atopic symptoms, with focus on the radiological findings. He presented with hematuria and dysuria and ultrasonography (US) showed irregular bladder wall thickening resembling a bladder mass. CT urography did not characterize the lesion any further and showed no local or distant spread. Biopsies revealed eosinophilic cystitis, a benign inflammatory condition. We found that US characterized the lesion at least as well as CT and should be the first choice of imaging. When staging is considered before biopsy, MRI should be preferred to CT. There are no specific radiological signs of eosinophilic cystitis. On follow-up, US was a safe, cost-effective imaging modality, but findings should be interpreted in a clinical context. In a child with hematuria and a bladder mass, eosinophilic cystitis is a relevant but rare differential diagnosis, especially when there is a known atopic history.